The concept of Islamic Literature by Prof. Dr. Hashim Awang - Yaacob, Adli (Global Academic Excellence (M) Sdn Bhd (GAE), 2021)
This article explains the concept of islamic literature by Prof. Dr. Hashim Awang. According to him, the concept of the Malay literature has the same theoretical concept of the Methodological theory of Malay but not all of them can be accepted. In order to find an ideal literacy, he presented two additional factors which are in literacy critisim and the reader as diakronis diversity (era). Besides that, he also introduced the History of the Methodological Theory because it emerges from a literature- one people have values and its own peculiarities. On the other hand, Prof. Dr. Hashim voice out his opinion that features of the Malay community that is closely associated with "natural", and this world is a part of their lives. According to him, the methodology is presented in the light of the way of life and attitudes, beliefs and culture of the local community, the Malay community that gave inspire to introduce idea to its own literary works. Based on this, he found the two methodologies that are deemed relevant and meaningful. First, methodological "Naturalists" and .)الطريقة العالمية والطريقة الدينية( "second; methodologies "religious